A Two Stage Oxidative Decarboxylation of di carboxylic acid by Pyridiniumdichromate in perchloric acid media - B K Dangarh, Shikha Soni, Shilpa Rathore (Journal of Medical Biomedical and Applied Sciences, 2016)
Oxidation of di carboxylic acid viz- tartaric acid by pyridiniumdichromate (PDC) in perchloric acid medium has been studied. Active oxidizing species involved is protonated PDC. First order plot log (a-x) versus time is broken in two straight lines. Some induction period is also observed. Effect of concentration of substrate, PDC, HClO4, Mn (II), Ce (III) and ionic strength has been investigated. Thermodynamic parameters have been evaluated. Energy of activation is 53.14 and 56.58 kJ mol-1 for two successive stages of oxidation. Entropy of activation is low and negative. Although the activation energy does not correspond to C-C bond breaking, but the reaction products indicate C-C bond breaking. Suitable mechanism has been proposed involving complex formation.